The Decline of German Economic Activities in Singapore During the First World War. - Azmi, Muhammad Aslah Akmal; Mohamed Dali, Azharudin; Zainol, Salina (History Department, Semarang State University and Historian Society of Indonesia, 2024)
This article analyzes the expansion of German economic activities in Singapore that the British administration restricted during the First World War. As the First World War broke out on 28 July 1914, trade relations between Germany and Singapore had to be terminated. This trade relationship ended due to Britain’s involvement in the First World War against Germany. Several war-related policies from the British Parliament were enacted to restrict German economic activity globally. During the war, Singapore, as one of the British colonies, had to implement war-related policies formulated by the British Parliament through several ordinances. Therefore, this article evaluates the extent to which the British administration successfully restricted German economic activities in Singapore through the legislation of several ordinances issued by the British Parliament. This study applies qualitative methods based on historical research methodology to examine British government documents and relevant secondary writings. The study's results found that efforts implemented by the British administration successfully ended the expansion of German economic activities in Singapore during the war.Artikel ini menganalisis perkembangan aktivitas ekonomi Jerman di Singapura yang dibatasi oleh pemerintahan Inggris pada Perang Dunia Pertama. Ketika Perang Dunia Pertama pecah pada 28 Juli 1914, hubungan dagang antara Jerman dan Singapura terpaksa ditamatkan. Berakhirnya hubungan dagang ini berpunca daripada keterlibatan Inggris dalam Perang Dunia Pertama melawan Jerman. Beberapa kebijakan terkait perang dari parlemen Inggris diberlakukan sebagai upaya untuk membatasi aktivitas ekonomi Jerman di tingkat global. Singapura sebagai salah satu jajahan Inggris juga menerapkan kebijakan terkait perang dari parlemen Inggris melalui penyusunan beberapa peraturan sepanjang masa perang. Oleh karena itu, artikel ini mengevaluasi sejauh mana keberhasilan pemerintahan Inggris di Singapura dalam membatasi aktivitas ekonomi Jerman di Singapura melalui beberapa peraturan yang dikeluarkan parlemen Inggris. Penelitian ini menerapkan metode kualitatif berdasarkan metodologi penelitian sejarah untuk mengkaji dokumen-dokumen Inggris dan tulisan sekunder yang relevan. Hasil penelitian menemukan bahwa pembatasan yang diterapkan oleh pemerintah Inggris berhasil mengakhiri perkembangan aktivitas ekonomi Jerman di Singapura selama masa perang.